Implementasi E-Commerce Bisnis Warung Klontong berbasis Android dengan menggunakan Algoritma Haversine Formula - Khairil Anam; Bayu Charisma Putra; Muhammad Aldi Firmansyah; Ferdy Muhammad Firdaus (Jurnal Teknologi Informasi dan Multimedia, 2025)
The influence and role of information technology in the Indonesian business sector is very large. With this technology, in today's era, people are required to live an efficient lifestyle, for example when making buying and selling transactions. However, this has an impact on small shops that are less competitive than online stores that can provide convenience in finding products and making shopping transactions. Grocery shops in Sidoarjo Regency are less competitive and experience a decline in consumer purchasing power due to the minimal use of E-Commerce on the development of their shop business. This study aims to determine the effect of Android-based Grocery Shop Business ECommerce using the Haversine Formula Algorithm. The targeted results of this activity are that by implementing this E-commerce application, people will be facilitated in various ways in making buying and selling transactions starting from finding the distance to the nearest shop, digital purchases, and the time spent. The test results from this study were carried out using the black box testing method. The testing process will be carried out on all functional needs that have been designed at the application design stage. The results of this research trial obtained a system accuracy of 100%, and received a rating of 74% as very good, 23% received a good rating and 3% received a sufficient rating from the results of user testing conducted on the haversine formula application.